Dorsal Thompson: Approach to the Proximal Radial Shaft. (August 2021) - Murphy, Meredith; Teasdall, Robert J.; Comadoll, Shea; Aneja, Arun
Abstract : Summary: Treatment principles in the management of radial shaft fractures, congruent with all fracture care, are to restore anatomy and function of the limb. Radial shaft fractures are unique in that preserving the anatomic bow of the radius, which allows for its rotation around the ulna during pronation and supination, is essential for proper function. The 2 main approaches for exposure of the proximal or middle third radial diaphyseal fractures are the volar "Henry" and the dorsal "Thompson." This article highlights the benefits of the dorsal Thompson approach, describes the key points of the operative technique, which allow for protection of the posterior interosseous nerve, and provides an overview of the measurable outcomes when using this approach. In the accompanying video, the steps of operative exposure to the proximal radial shaft with careful avoidance of the posterior interosseous nerve are demonstrated.